Morphological and anatomical properties of Veronica crista-galli Steven - Pashayeva, Nigar Hidayet; Suleymanov, Tahir Abbasali; Kerimov, Yusif Balakerim; Gasimov, Eldar Kocheri; Rzayev, Fuad Huseynali (ScienceRise: Biological Science, 2021)
The aim of this work was to study of diagnostic signs of the morphological and anatomical structure of Veronica crista-galli Steven. from the flora of Azerbaijan. Materials and methods. The samples for research were collected during their flowering time in June 2018, in the Ismailli region of the Republic of Azerbaijan. Plant samples were fixed in a solution made in 0.1 M phosphate buffer (pH=7.4), containing 2.5 % glutar-aldehyde, 2.5 % paraformal-aldehyde and 0.1 % picric acid. In the next stage was the preparation of block and their filling in Araldite – Epon according to the TEM method. Results. The leaf is simple, lower part is short-petiolate and upper is sessile. The surface, on both sides of the leaf, is reliefly, and 7–8 conductive veins are clearly visible. The lower and upper sides of the leaf, and also margin, are strewn with multicellular hairs. The calyx of the flower consists of two sepals which grown together at the base, covered with simple multicellular hairs. The stalk in is a long filiform. The corolla of flower consists of 4 petals which grown together at the base and 2 stamens attached to the tube of the corolla. On the epidermis, cells with sinuous and bead-like walls, numerous stomata of the stavrocytic type, capitate hairs are visible. From the cross section of the leaf, it is visible that palisade tissue at the upper and sponge tissue at the bottom. Conclusions. As a result of morphological and anatomical studies, it was revealed that diagnostic signs of plant raw material can be: Present of multicellular hairs on the leaf blade; The location of the capsule between the sepals; Stavrocytic type of the stoma structure; The bead-like walls of the epidermis; Capitate hairs on the epidermis; Sepals covered by hairs. The established anatomical diagnostic features can be used for the drafting of the normative document on the plant raw materials and for identification of plant raw material of Veronica crista-galli